Pengaruh Metode Bercerita Terhadap Kemampuan Bahasa Pada Anak Kelompok B di TK Yapis Merauke - Cristiana Normalita de Lima; Dharma Gyta Sari Harahap; Damaris Marlissa (Institut Nalanda, 2023)
This study aims to determine whether there is an effect of the storytelling method on language skills in group B children at Yapis Merauke Kindergarten. This study used an experimental research type, with a pre-experimental research design in the form of a One Group Pretest-Posttest Design. The population of this study was all of the children in Group B at Yapis Merauke Kindergarten in the academic year 2022/2023 totaling 40 children who were divided into 2 parallel classes namely classes B1 and B2 and the research sample was children from group B1 with a total of 20 children taken using a probability sampling technique with a simple type random sampling. Data analysis used paired sample t-test. The research results obtained t count = 13.2587 greater than t table = 1.72913 which means H0 is rejected and Ha is accepted so it can be concluded that there is an influence on children's language skills using the storytelling method in Group B1 Kindergarten Yapis Merauke.